Secondary Amyloidosis Presenting as Ischemic Proctitis - Saad Hashmi; Assad Munis; Ryan T. Hoff; Hymie Kavin; Eli D. Ehrenpreis (Case Reports in Gastrointestinal Medicine)
A 49-year-old man presented with abdominal pain and rectal bleeding for two days associated with a 50-pound unintentional weight loss. History was notable for hypertension, chronic kidney disease, obesity, gout, and acute cholecystitis status post cholecystectomy. Computed tomography (CT) of the abdomen and pelvis showed rectal wall thickening. Colonoscopy showed proctitis with superficial ulcerations. In the setting of renal insufficiency, malabsorption, and low-voltage QRS complexes on electrocardiogram (ECG), amyloidosis was considered in the differential diagnosis. Rectal and renal biopsies with subsequent retrospective staining of gallbladder tissue confirmed amyloid deposition. Gastrointestinal involvement of amyloidosis is relatively uncommon. Particularly, amyloid deposition in the gallbladder and rectum is very rare. The development of AA amyloidosis in our patient may have been related to gout, obesity, and the presence of a heterozygous complex variant for the MEFV (familial Mediterranean fever) gene. Awareness of this atypical presentation of amyloidosis is important, as additional staining of biopsy samples is necessary, and diagnosis allows for directed treatment.